Major accidents to the environment a practical guide to the Seveso II directive and COMAH regulations - Vince, Ivan. (Butterworth-Heinemann, 2008)
If our plant catches fire, when should it be allowed to burn down to prevent pollution? When does enforcement turn into prosecution, following an environmental accident? Will our environmental insurance cover the costs of remediation? This book provides a thorough and practical guide to the environmental aspects of compliance with the Seveso II Directive and COMAH regulations and surrounding issues. It guides readers through the technical, legal and insurance related complexities unique to the environmental aspects of Seveso II/COMAH. Individual chapters and sections written by relevant experts explain the implications of the Directive/Regulations and other laws that relate to major accident hazards. Valuable case studies underpin and illuminate the arguments presented. The comprehensive appendices contain a wealth of further case studies as well as focused supporting information on environmental design, assessment and management of major hazard installations, for safety, prevention and environmental professionals, risk assessors, insurers, managers and their legal advisors. Dr Ivan Vince is Director of ASK Consultants and co-founder of one of the first industrial risk consultancies in Eastern Europe. He has investigated several environmental accidents. Related titles: Introduction to Emergency Management, 2e Haddow and Bullock 978-0-7506-7961-9 Introduction to International Disaster Management, Coppola 978-0-7506-7982-4 Learning from Accidents, 3e, Kletz 978-0-7506-4883-7 * This is only guide to working with and implementing the Seveso II-Directive and COMAH (Control of Major Accident Hazards) regulations * Written by leading risk management, scientific, legal, and engineering experts, this book provides all of the key elements an organisation must manage in order to comply * Accompanied by a comprehensive data handbook that enables managers and health & safety professionals to assess and apply the approaches required in the Directives.